Meningkatkan Hasil Belajar Pendidikan Agama Katolik Melalui Model Problem Based Learning Berbantukan Media Wordwall Game Kelas 5 SD Santo Yoseph 1 Medan - Janes Saroha Sihotang (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve the learning outcomes of Catholic Religious Education for 5th-grade students at SD Santo Yoseph 1 Medan through the implementation of the Problem Based Learning (PBL) model supported by the interactive media Wordwall Game. The research method used is Classroom Action Research (CAR), conducted in two cycles, with each cycle comprising planning, action, observation, and reflection. Data collection was carried out through learning outcome tests, observation, and documentation. The results indicate an improvement in student learning outcomes from Cycle 1 to Cycle 2. In Cycle 1, the average student score was 81.5, while in Cycle 2, it increased to 91. The application of the PBL model with the Wordwall Game media proved to be effective in enhancing student engagement and learning outcomes. This improvement was driven by a more engaging and interactive learning process, as well as the students' ability to think critically and solve problems. Therefore, the PBL model with the support of Wordwall Game can be widely implemented to improve learning quality.